Randomized clinical trial between Fluoxetine and Dapoxetine for premature ejaculation and its effect on marital relationship - Che' Man, Mohamad; Mohd Zin, F; Che Alhadi, Shahidah; Yaacob, Najib Majdi; Ismail, Shaiful Bahari (IIUM Press, 2021)
INTRODUCTION: Premature ejaculation(PE) decreases sexual pleasure and quality of life, and both Fluoxetine and Dapoxetine were used in PE therapy. Dapoxetine is the first SSRI with a short half-life and fewer side effects, primarily designed for PE therapy. The aim is to evaluate and compare the effects of Fluoxetine and Dapoxetine on PE symptoms and marital satisfaction. MATERIALS AND METHODS:44 participants aged between 18 and 64 with a PEDT score of ≥9 from Hospital USM's Primary-Care-Clinic, Kelantan Malaysia were selected and randomized into two groups: Fluoxetine(FG) and Dapoxetine Group(DG), and administered for 8 weeks with either regular Fluoxetine(20mg) or Dapoxetine (30mg) on-demand at least once a week. Premature Ejaculation Diagnostics Tool(PEDT) score was used to assess PE symptoms and Dyadic Satisfaction-Dyadic Adjustment Scale(DS-DAS) used to evaluate marital satisfaction at baseline and the 8thweek. RESULT: 22 and 21 participants in FG and DG completed the study. For both groups, PEDT scores decreased substantially [from 11.41 to 5.45(P<0.001) among FG, from 13.43 to 3.10(P<0.001) among DG]. After adjustment of the baseline PEDT score, PEDT scores in DG(6.03 vs 2.49, P<0.001) were lower at the 8th week. All groups showed significantly improved DS-DAS scores [from 34.50 to 40.68(P<0.001) in FG, from 36.57 to 44.33(P<0.001) in DG]. No marked difference in DS-DAS was scored after adjustment of the baseline DS-DAS score(41.13 vs 43.86, P=0.055) at the end of the assessment. CONCLUSION:Treatment of PE with either Fluoxetine or Dapoxetine decreases PE symptoms and increases marital satisfaction.